Endogenous Steroid Induced Glaucoma due to Cushing Syndrome - Singh, Kirti; Dangda, Sonal; Ahir, Nitasha; Bhattacharyya, Mainak (Journal of Ocular Diseases and Therapeutics, 2014)
Exogenous steroid usage is a documented cause of increase in intraocular pressure in susceptible individuals; with systemic use having a lower propensity than topical. Endogenous hypercortisolism is an uncommon cause of steroid induced glaucoma with few reported cases due to adrenal adenoma, ectopic ACTH production in para-neoplastic syndromes, and pituitary adenomas. We report a case of steroid induced glaucoma occurring due to adrenal hyperplasia with confounding feminizing features which caused a diagnostic dilemma.